Contractor Prequalification Model for Lean Project Delivery - Ibrahim Bakry; Esraa Daoud (International Journal of Supply Chain Management, 2019)
Waste rates in the construction industry are high and this affects the cost, time, safety and quality of construction projects. Waste occurs through every construction development stage starting from inception, through design, procurement and supply, construction and operation stages. To improve the performance of construction projects, a model is developed to facilitate a more comprehensive implementation of Lean principles starting from contractor or supplier prequalification stage. The model ranks interested contractors or suppliers based on assessing their ability to deliver/participate in Lean projects. Factors required for the assessment are extracted from literature, AHP is utilized to compare and rank factors according to their importance. Then the ranked factors are used to score different contractors ability to deliver Lean projects. The outcome of this model is a ranking of the contractors from the highest Lean practitioner to the lowest based on the total weighted score. To evaluate the model a questionnaire was designed and distributed among different international contractors, the questionnaire asked contractors basic questions about their companies and submittals from each contractor were then evaluated by construction experts. The results show the models ability to rank contractors according to their pre-established experience in delivering Lean projects.